2020
DOI: 10.7146/torture.v30i2.119199
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a combined psychotherapy and physiotherapy group treatment program for survivors of torture incarcerated in an adult prison in Kurdistan, Iraq: A pilot study

Abstract: Introduction: Survivors of torture have high rates of mental health problems and can experience a sequela of physical effects with the most common being persistent pain. Similar to survivors of torture, persons that are incarcerated have high rates of mental health problems, persistent pain and pain-related disability.The purpose of this study is to assess the effect of an interdisciplinary group treatment approach, involving psychotherapy and physiotherapy, with survivors of tortur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…One of the factors reported in the study for the onset or worsening of these disorders is the psychosocial experience of prison, and torture and other cruel treatments certainly contribute to the worsening of this scenario. It has even been shown that survivors of torture have high rates of mental illness (Gamble et al, 2020). A systematic review corroborated the results of this research by concluding that female prisoners are at higher risk for physical and mental health problems (McGinley & McMillan, 2019).…”
Section: Discussionsupporting
confidence: 54%
“…One of the factors reported in the study for the onset or worsening of these disorders is the psychosocial experience of prison, and torture and other cruel treatments certainly contribute to the worsening of this scenario. It has even been shown that survivors of torture have high rates of mental illness (Gamble et al, 2020). A systematic review corroborated the results of this research by concluding that female prisoners are at higher risk for physical and mental health problems (McGinley & McMillan, 2019).…”
Section: Discussionsupporting
confidence: 54%
“…Three trials were conducted at clinics serving refugees in Europe or the United States, and one trial was conducted in an Iraqi prison ( Table 1 ). In total, the four trials included 114 men and 196 women, with one trial only including men [ 34 ]. The ages of participants ranged from 18 to 65 years, and three studies reported an average age range of 31–48 years [ 34 , 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, the four trials included 114 men and 196 women, with one trial only including men [ 34 ]. The ages of participants ranged from 18 to 65 years, and three studies reported an average age range of 31–48 years [ 34 , 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is not one single method available that can address the pain and discomfort that can be experienced by persons with a traumatic background. A broad and contextual understanding of concepts of pain are therefore paramount (Gamble et al, 2020). The aim must be to create opportunities to change for the better, which might require additional measures and use of a more holistic approach.…”
Section: Pain Managementmentioning
confidence: 99%